Bleach. 36, Turn back the pendulum - Kubo, Tite; Caselman, Lance (Kubo, Tite. Bleach (VIZ Media), 2011)
"Find out what happened in the Soul Society one hundred years ago. Kisuke Urahara is the new captain of twelfth company--now if only he could get along with his assistant captain. And Soul Reaper captain Shinji Hirako suspects something sinister is going on with his second in command, Aizen." --p.[4] of cover.